The Effect of Work Balance and Teacher’s Engagement on Teacher’s Performance - Yuni, Umi Rima; Ahyani, Nur; Wahidy, Achmad (Yayasan Sembilan Pemuda Indonesia, 2024)
The purpose of this study was to determine the effect of work balance and work attachment on the performance of elementary school teachers in the Gugus 2 Koba sub-district, Central Bangka Regency. The sample size taken was 94 elementary school teachers of elementary school teachers in Gugus 2 Koba District, Central Bangka Regency. The sampling technique was purposive sampling, where the respondents were some of the Primary School Teachers of Gugus 2 Koba Sub-district, Central Bangka Regency. Data collection was carried out by distributing questionnaires using a 5-point Likert scale to measure 75 statement items. The analysis technique used was multiple linear regression analysis. The results showed that there was an influence of Work Balance and Work Attachment on Teacher Performance. Second, there is an influence of work balance on teacher’s performance third there is an influence of teacher attachment on teacher’s performance.